Parental income and children's smoking behaviour: Evidence from the British household panel survey - Laura Blow; Andrew Leicester; Frank A. G. Windmeijer (Institute for Fiscal Studies (IFS), 2005)
Does money matter? When investigating health behaviour, research often finds a strong positive association between income and healthy behaviour. This could however be due to individual characteristics that determine both income and health investment and is not necessarily due to the role of money per se. In this study we look at this relationship over the generations by studying the association between parental income and children's prevalence to smoke in Britain using data from the British Household Panel Survey and British Youth Survey. We find an inverse relation between parental income and children's smoking prevalence, but when looking at within household changes by comparing sibling's smoking status differences at the same age, we find instead a positive effect. This indicates that within household increases in income lead to an increased probability of smoking of a younger child.
Keywords: I12; C23; 330; Child smoking; Parental income; Panel Data; Rauchen; Kinder; Haushaltseinkommen; Großbritannien